Vietnamese English teachers’ views on formative assessment management and suggestions to improve student motivation - Hai, Nguyen Van (Linguistics and Culture Review, 2021)
Student performance assessments play an important role in the training process. They reflect how well students performed their learning activities. The goals of assessment are multiple according to their functions. Among assessment forms currently applied at higher education institutions, the formative assessment shows its strength over others by offering great contributions to the innovation of teaching and learning activities. Appropriate use of this form of assessment leads to a successful teaching and learning process, and a much better result and quality of training. This paper focuses on the view of formative assessment management from teachers’ lenses in order to help adjust teaching/learning methods and curriculums. To learn more about the reality of formative assessment for English majors and how it is managed by various stakeholders, a questionnaire and interviews were used. The investigation's findings reveal a substantial lack of teacher knowledge of the nature and strengths of formative assessment. These findings also point to new ways to increase student motivation through the use of formative assessment.